2019
DOI: 10.1097/dad.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Immunohistochemical Study of 14 Cases of Morbihan Disease: An Insight Into Its Pathogenesis

Abstract: Introduction: Morbihan disease (MORD) is rare with only 45 clear-cut cases previously reported. Histopathologic findings are supposed to be nonspecific. We report 14 patients and review the previous cases. Objectives: To characterize the clinicopathologic findings, outcomes, and immunophenotype of MORD. Material and Methods: Inclusion criteria were a clinical picture of persistent, nonpitting edema affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 32 publications
2
17
0
5
Order By: Relevance
“…The pathogenic mechanisms of Morbihan syndrome are unclear, and some dermatologists recognized it as one of complications of rosacea[ 9 ]. However, there are also some reported cases of Morbihan syndrome that show no clinical manifestations of rosacea, which are similar to our case[ 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…The pathogenic mechanisms of Morbihan syndrome are unclear, and some dermatologists recognized it as one of complications of rosacea[ 9 ]. However, there are also some reported cases of Morbihan syndrome that show no clinical manifestations of rosacea, which are similar to our case[ 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…Pathogenesis of solid facial oedema remains unclear, although lymphatic dysfunction is likely to play an important role [8]. Ramirez-Bellver et al [9] showed that in cases of Morbihan disease, histopathological examination may reveal oedema of the dermis, presence of dilated lymphatic vessels in the upper layers of the dermis expressing D2-40 and CD31 antigens, presence of mast cells, and, less frequently, granulomatous lymphangitis. These features correspond to localised lymphoedema; therefore, it is necessary to differentiate it from other diseases associated with lymphoedema, including Melkersson-Rosenthal syndrome [9].…”
Section: Discussionmentioning
confidence: 99%
“…Ramirez-Bellver i wsp. [9] wykazali, że w przypadkach choroby Morbihan badanie histopatologiczne może ujawnić obrzęk skóry właściwej, obecność poszerzonych naczyń limfatycznych w górnych warstwach skóry właściwej wykazujących ekspresję antygenów D2-40 i CD31, mastocytów i rzadziej -ziarniniakowe zapalenie naczyń chłonnych. Cechy te odpowiadają zlokalizowanemu obrzękowi chłonnemu, dlatego konieczne jest różnicowanie z innymi chorobami przebiegającymi z obrzękiem chłonnym, w tym z zespołem Melkerssona-Rosenthala [9].…”
Section: Discussionunclassified
See 2 more Smart Citations